Sudden unexpected infant death syndrome in Ribeirão Preto, Brazil - Peres, Luiz Cesar (São Paulo Medical Journal, 1998)
CONTEXT: Sudden Infant Death Syndrome (SIDS) is the leading cause of death in the first year of life in developed countries. Brazilian and Latin American literature lack studies on the subject, which is largely unknown among health workers. OBJECTIVE: To identify cases that could be classified as SIDS among children of less than one year of age submitted to autopsy at the Serviço de Verificação de Óbitos do Interior (SVOI), in Ribeirão Preto, SP, Brazil. A retrospective analysis of all autopsies from SVOI in this age group from January 1987 to December 1990 was done. RESULTS: There were 369 autopsies of which 344 (93.2%) deaths were expected and 25 (6.8%) unexpected. From the 25 unexpected cases 16 (64%) deaths could not be explained after autopsy and from these cases only 10 were eligible for the study because they had full organ sampling. There were 7 males and 3 females and the age at death ranged from 1 to 3 months (average: 1.7 months). Two were found dead, 3 died at home, 4 died on the way to hospital and 1 died while being fed. Autopsy diagnoses were aspiration (8 cases), SIDS (1 case) and undetermined (1 case). Aspiration was not confirmed by histology and the only findings were mild pulmonary edema, subcapsular petechiae and intraparenchymatous hemorrhage in thymus. CONCLUSION: That there were 10 cases of unexpected and unexplained deaths of children less than 1 year-old during the evaluated period with characteristics similar to SIDS which should therefore be classified as such.